African Medicinal Plants that Can Control or Cure Tuberculosis - Philip Ifesinachi Anochie; Bakoh Ndingkokhar; Juan Bueno; Felix Emeka Anyiam; Linus Ndidi Ossai- Chidi; Edwina Chinwe Onyeneke; Anthony Chidiebere Onyeozirila (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2018)
This review contains a compendium of medicinal plants in Africa that can control or cure tuberculosis. A good number of plant secondary metabolites are reported to have antitubercular activity comparable to the existing antitubercular drugs or sometimes even better. Information regarding the chemistry and pharmacology of plants leads to insight into their structure-activity relationship and potency. A welldefi ned strategy is required to exploit these phytomolecules as antitubercular drugs.